2022
DOI: 10.1007/s00520-022-07334-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychological variables associated with quality of life in patients with head and neck cancer: the role of body image distress

Abstract: Objective The aim of this cross-sectional study was to explore the relationship between quality of life (QoL) and body image distress in patients with head and neck cancer (HNC), considering relevant psychological variables (i.e., coping strategies, social anxiety symptoms, self-esteem, intolerance of uncertainty, pain, and distress). We also aimed to explore gender differences in patients with HNC in terms of relevant psychological variables in HNC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…A self-reported questionnaire was used to assess body image stress, physical and mental quality of life, and psychological variables. Females also showed lower mental quality of life and self-esteem compared to males 13 . Another study done by Gautam S and Pudel A. on the effect of gender on the psychosocial adjustment of colorectal cancer survivors showed that both genders had significant impairment in psychosocial adjustment.…”
Section: Discussionmentioning
confidence: 93%
“…A self-reported questionnaire was used to assess body image stress, physical and mental quality of life, and psychological variables. Females also showed lower mental quality of life and self-esteem compared to males 13 . Another study done by Gautam S and Pudel A. on the effect of gender on the psychosocial adjustment of colorectal cancer survivors showed that both genders had significant impairment in psychosocial adjustment.…”
Section: Discussionmentioning
confidence: 93%
“… 1 , 2 Throughout their diagnosis, treatment, and recovery from the illness, many of them have significant psychological or physical side effects such as pain, stress, sadness, anxiety, and distress. 3 , 4 Thirty percent of breast cancer patients have anxiety, and 70% report suffering distress while going about their regular lives. 5 , 6 Fifty-nine percent of cancer survivors say they have a moderate to high level of concern about their disease returning.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Negative body image in patients with cancer leads to psychological problems, including depression, anxiety, and distress, 2 as well as changes in family functioning and social relationships, 3 resulting in a decrease in the overall quality of life. 4 Although the body image of patients with cancer differs by individual, the degree of body image alteration varies depending on the visibility and reversibility of physical changes and the affected body parts, in general. 1 …”
Section: Introductionmentioning
confidence: 99%
“… 6 Moreover, women tend to be more sensitive to body changes than men. 4 Therefore, the diagnosis and treatment of breast cancer significantly affect the body image of women.…”
Section: Introductionmentioning
confidence: 99%